2018
DOI: 10.1186/s13570-018-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of predisposing factors on microbial loads in camel milk along the pastoral dairy value chain in Kenya

Abstract: The aim of this study was to map the camel milk value chain and establish the predisposing factors for increase in microbial counts in milk along the chain. Isiolo County was chosen for the study. Data collection was done through key informant interviews, structured interview schedules, observation and microbial analysis of milk samples. During milk sampling, milk temperature, environmental temperature, time and volume of milk from which the sample was taken were recorded. Along the value chain, microbial coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…According to the 2019 census, Isiolo central had the highest population, with 121,066 persons, Garbatulla had 99,730 persons, and Merti had the lowest population with 47,206 persons. In terms of climate and land-use system, Isiolo County is a typical arid and semi-arid region with a bimodal rainfall pattern, characterized by long rains from March to May, and short rains from October to December (Nato et al, 2013(Nato et al, , 2018Noor et al, 2013). The temperatures are high throughout the year, ranging from a mean minimum of 27 o C and a maximum of 30 o C, in almost all parts of the county (Nato et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the 2019 census, Isiolo central had the highest population, with 121,066 persons, Garbatulla had 99,730 persons, and Merti had the lowest population with 47,206 persons. In terms of climate and land-use system, Isiolo County is a typical arid and semi-arid region with a bimodal rainfall pattern, characterized by long rains from March to May, and short rains from October to December (Nato et al, 2013(Nato et al, , 2018Noor et al, 2013). The temperatures are high throughout the year, ranging from a mean minimum of 27 o C and a maximum of 30 o C, in almost all parts of the county (Nato et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of climate and land-use system, Isiolo County is a typical arid and semi-arid region with a bimodal rainfall pattern, characterized by long rains from March to May, and short rains from October to December (Nato et al, 2013(Nato et al, , 2018Noor et al, 2013). The temperatures are high throughout the year, ranging from a mean minimum of 27 o C and a maximum of 30 o C, in almost all parts of the county (Nato et al, 2018). About 95% of the county is classified as arid or very arid, while only 5% is semi-arid, generally receiving an average annual rainfall below 300 mm (12 inches), which is also unevenly distributed (National Drought Management Authority, Ministry of Devolution and Planning, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Nato et al (2018) to assess predisposing factors on microbial loads in milk, found that along with the value chain microbial counts increased as milk was held at 28 to 33 o C before cooling.…”
mentioning
confidence: 99%